Enhancing Financial Inclusion in the MSME Sector: An Investigation of Fintech Adoption in Indonesia through Structural Equation Modeling - Vidya Purnamasari; Linda Seprillina; Vika Annisa Qurrata; Tamat Sarmidi; Nila Cahayati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to critically analyze the determinants of fintech adoption among micro, small, and medium-sized enterprises (MSMEs) in Indonesia, utilizing the robust Structural Equation Modelling (SEM) method. Financial Technology (fintech) represents a disruptive innovation that is transforming traditional banking and financial services by integrating digital financial products and services, including payment transactions and security systems such as e-payments, peer-to-peer lending, remittances, crowdfunding, and retail investment. The research focuses on four key variables: the Decision to Use Fintech (DUF) as the dependent variable, and three independent variables —Perceived Ease of Use of the Fintech Platform (POE), Perceived Risk (POR), and Benefits Offered/Sales Promotion (BP). Data was collected via surveys from owners and managers of MSMEs in Malang City, East Java, Indonesia. The findings reveal that the ease of use and time-saving features of fintech significantly influence adoption decisions among MSMEs, underscoring its positive impact on business operations and economic efficiency. Conversely, perceived risks and promotional benefits were found to have no significant effect on the decision to adopt fintech platforms.